DOI: 10.4018/978-1-4666-6090-8.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Movement Estimation Based on Suprahyoid Muscle Activity

Abstract: The motor function of the tongue often remains intact even in cases of severe movement paralysis. Therefore, tongue movements offer great potential for the design of highly efficient human-machine interfaces for alternative communication and control. This chapter introduces a novel method for tongue movement estimation based on analysis of surface electromyography (EMG) signals from the suprahyoid muscles, which usually function to open the mouth and to control the hyoid position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, in a study that ultrasonographically evaluated tongue movement capability during mastication [9], tongue movement dynamics were difficult to analyse quantitatively, and the details of the relationship between tongue movement during mastication and masticatory efficiency were not clarified. As for the relationship between tongue movement and the suprahyoid muscles, Sasaki, et al, [10] evaluated five basic movements of the tongue left, right, forward, opening and saliva swallowing movements using a nine-channel electrode array and reported that the action potential of the suprahyoid muscles reflected the tongue movements with a high probability.…”
Section: Introduction and Propositionmentioning
confidence: 99%
“…Furthermore, in a study that ultrasonographically evaluated tongue movement capability during mastication [9], tongue movement dynamics were difficult to analyse quantitatively, and the details of the relationship between tongue movement during mastication and masticatory efficiency were not clarified. As for the relationship between tongue movement and the suprahyoid muscles, Sasaki, et al, [10] evaluated five basic movements of the tongue left, right, forward, opening and saliva swallowing movements using a nine-channel electrode array and reported that the action potential of the suprahyoid muscles reflected the tongue movements with a high probability.…”
Section: Introduction and Propositionmentioning
confidence: 99%